2012
DOI: 10.1038/ng.1069
|View full text |Cite
|
Sign up to set email alerts
|

ABCB6 is dispensable for erythropoiesis and specifies the new blood group system Langereis

Abstract: The human ATP-binding cassette (ABC) transporter ABCB6 has been described as a mitochondrial porphyrin transporter essential for heme biosynthesis1, but is also suspected to contribute to anticancer drug resistance2–4, as do other ABC transporters located at the plasma membrane. We identified ABCB6 as the carrier of the blood group antigen Lan on red blood cells, but also at the plasma membrane of hepatocellular carcinoma (HCC) cells, and established that ABCB6 actually encodes a new blood group system (Langer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
178
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(184 citation statements)
references
References 18 publications
4
178
0
2
Order By: Relevance
“…Confocal microscopy analysis showed that ABCB6 was expressed at the RBC membrane, and colocalized in some membrane regions with CD55 (Decay Accelerating Factor bearing the Cromer blood group system) (Fig. 3C), in agreement with the recently published results [21]. We further confirmed ABCB6 localization in the red cell membrane by substantial colocalization with glycophorin A in control red cells (Fig.…”
Section: Structural Modeling Of Wild-type and Mutant Abcb6supporting
confidence: 92%
See 1 more Smart Citation
“…Confocal microscopy analysis showed that ABCB6 was expressed at the RBC membrane, and colocalized in some membrane regions with CD55 (Decay Accelerating Factor bearing the Cromer blood group system) (Fig. 3C), in agreement with the recently published results [21]. We further confirmed ABCB6 localization in the red cell membrane by substantial colocalization with glycophorin A in control red cells (Fig.…”
Section: Structural Modeling Of Wild-type and Mutant Abcb6supporting
confidence: 92%
“…This protein was recently identified in the RBC membrane [20], where it displays the Langereis blood group [21].…”
Section: Introductionmentioning
confidence: 97%
“…57 Moreover, in erythrocyte membranes it bears the Langereis (Lan) blood group antigen system. 58,59 ABCB6 expression increases during erythroid differentiation of CD34+ cells. 56 The ABCB6 missense mutations in FP does not alter mRNA or protein levels, or subcellular localization in mature erythrocytes or erythroid precursor cells, but are predicted to have a pathogenic consequence on protein function.…”
Section: Familial Pseudohyperkalemia and Cryohydrocytosismentioning
confidence: 99%
“…31 However, in two more recent studies, several individuals homozygous for deleterious loss of function mutations, including frameshift and nonsense mutations, were found to have a newly identified rare Lan blood group antigen. There were no reports of coloboma or eye defects in individuals homozygous or heterozygous for these variants 32 . In our family (Family 10), the unaffected father also carried ABCB6, c.575G4A (p.(Arg192Gln)) in the heterozygous state, indicating that this is a variant with incomplete penetrance and that other factor/s are contributing to the disease phenotype in Patient 10.…”
Section: Exome and Target Region Analysismentioning
confidence: 99%